Problems of objects of unfinished building construction. Consideration and analysis of existing methods of risk-management assessment on the way of typechoosing of renovation of unfinished building construction. - Donenko, V.; Lukianova, T.; Lukyanchyk, A. (Ways to Improve Construction Efficiency, 2019)
Analyzed generalized list of criteria and indicators, which characterizing the efficiency of estimation of objects unfinished construction. Revealed application of risk management in projects of renovation. Outlined and formulated the main reasons for the imperfection of existing approaches to risk management. Determined basic quantitative and qualitative methods of risk management in the investment and construction sphere are determined. The peculiarities of their application are analyzed and revealed.